MATHEMATICAL MODELING OF THE PRESSURE AND TEMPERATURE EFFECT ON ELASTIC WAVE VELOCITY IN JOINTED ROCKS - Maslov B.P.; Prodaivoda G.T.; Vizhva S.A. (My University, 2001)
A new method is proposed for establishing effective thermoelastic constants as functions of pressure and temperature in rocks. The method is based on generalisation of the method of conventional moment functions, using Mori-Tanaka's calculations. The numerical results obtained for a peridotite sample by inversion of the dependence of longitudinally polarised waves on pressure and temperature agree well with experiment.